The biopsychosocial materno-semiotics framework: A holistic analytical tool for film studies - J. Priyadharshini; R. K. Jaishree Karthiga (MethodsX)
This study introduces the BPS Materno-Semiotics Framework, an innovative methodological approach that combines the Biopsychosocial (BPS) Model (Engel, 1977) with Semiotic Analysis (Barthes, 1964) to examine how films construct maternal distress. The portrayal of maternal or postpartum mental health in films continues to be crucial yet an underexplored area in the interdisciplinary studies. Studies that already exist don't combine cultural symbolism or psychological realism into a single analytical framework (Mayang & Aziz, 2023). This study bridges the gap and uses the movie Nightbitch (2024) as an example to show how biological, psychological, and social factors interact with cultural ideas about motherhood in film narratives.This comprehensive tool is useful for academics and filmmakers to evaluate how film influences public views of motherhood. It is flexible to be modified to analyse themes including mental health, workplace stress, and gender roles on other media portrayals. • This study offers a multifaceted methodology for the analysis of motherhood and mental health topics. • By integrating clinical psychology and cultural studies, this study provides an interdisciplinary framework. • This holistic tool enables to perform a dual-lens analysis that examines the psychological realities of parental inadequacies and the socio-cultural myths weaved into film portrayals.